Prevalence of respiratory morbidities and lung function outcome in Traffic Police in eastern Nepal - Koirala, Puru; Kumar Mehta, Ram; B Parajuli, Surya (Birat Journal of Health Sciences, 2024)
Introduction: Outdoor air pollution is a cause for occupational lung disease. A community vulnerable to lung health hazards of outdoor air pollutants from vehicle emissions is traffic police, whose long duration of outdoor work, with no proper protective equipment, predisposes them to respiratory symptoms such as cough, dryness of nose, throat irritation and wheezing due to the air pollutants causing inflammation of the airways. The risks to lung function and development of respiratory disease are not known in traffic police in eastern Nepal. Objectives: To determine respiratory morbidities and lung function values of traffic police working in eastern Nepal. Methodology: This cross-sectional study was conducted for 6 months, from 1st January to 30th June 2022, in traffic police using a structured questionnaire adapted from American Thoracic Society and National Heart & Lung Institute and portable spirometry, at the duty posts or office. Data were represented using descriptive statistics. Results: The study enrolled 129 traffic police in eastern Nepal, 109 (84.50%) were male and 20 (15.50%) females, mean age 34.50 (±8). Mean duration of active duty was 9.76 years (±6.19). Cough was present in 33 (25.58%), 50 (38.76%) phlegm, 37 (28.68%) dyspnea, and 28 (21.71%) noisy breathing. Mean FEV1% in ≤ 5 years exposure was 76.75 (±17.28), and 65.26 (±18.88) in > 15 years. Mean FVC% in ≤ 5 years exposure was 81.81 (±20.56) and 76.18 (±19.77) in those working >15 years. Mean FEF25-75% in ≤ 5 years was 73.69 (±23.73), which was 62.04 (±33.97) in those > 15 years. The spirometry analysis suggested obstructive airways disease in 90 personnel (69.8%), restrictive disease in 80 (62%), mixed airways disease in 72 (55.8%), and small airways disease in 52 (40.3%). Conclusion: There was increased burden of respiratory problems such as cough with sputum production, noisy breathing, and dyspnea and lower lung volumes and flows among traffic police working in different parts of eastern Nepal. Long duration of exposure to traffic environments resulted in spirometry analyses suggestive of obstructive and restrictive airways diseases.